(untitled) - Marcus, Ben (Guilford, Connecticut, 2017)
Mavericks and more, a celebration of feminine beauty, athleticism, wisdom, and skill when the surf is bombing—Women Who Surf profiles some of the world’s most inspiring female surfers ranging from Bethany Hamilton to Wrenna Delgado. Each surfer tells her story, highlighting her personal challenges, accomplishments, and philosophy, as well as inspiring readers and providing them with practical how-to suggestions on maximizing not only their own potential in surfing but in life as they lead the charge and push their limits at infamous big-wave spots like Teahupoo in Tahiti, Waimea Bay, and Peahi/Jaws in the Hawaiian Islands.
Keywords: Nữ vận động viên lướt sóng,Women surfers; Tiểu sử,Biography